Feasibility study on cardiac arrhythmia ablation using high-energy heavy ion beams - Lehmann, Helge Immo; Graeff, Christian; Simoniello, Palma; Constantinescu, Anna; Takami, Mitsuru; Lugenbiel, Patrick; Richter, Daniel; Eichhorn, Anna; Prall, Matthias; Kaderka, Robert; Fiedler, Fine; Helmbrecht, Stephan; et al. (Scientific reports, 2016)
High-energy ion beams are successfully used in cancer therapy and precisely deliver high doses of ionizing radiation to small deep-seated target volumes. A similar noninvasive treatment modality for cardiac arrhythmias was tested here. This study used high-energy carbon ions for ablation of cardiac tissue in pigs. Doses of 25, 40, and 55 Gy were applied in forced-breath-hold to the atrioventricular junction, left atrial pulmonary vein junction, and freewall left ventricle of intact animals. Procedural success was tracked by (1.) in-beam positron-emission tomography (PET) imaging; (2.) intracardiac voltage mapping with visible lesion on ultrasound; (3.) lesion outcomes in pathohistolgy. High doses (40-55 Gy) caused slowing and interruption of cardiac impulse propagation. Target fibrosis was the main mediator of the ablation effect. In irradiated tissue, apoptosis was present after 3, but not 6 months. Our study shows feasibility to use high-energy ion beams for creation of cardiac lesions that chronically interrupt cardiac conduction.